Foliar application of fullerenol and zinc oxide nanoparticles improves stress resilience in drought-sensitive Arabidopsis thaliana - Ana Joksimović; Danijela Arsenov; Milan Borišev; Aleksandar Djordjević; Milan Župunski; Ivana Borišev (PLoS ONE, 2025)
This study aimed to characterise the chemical properties of fullerenol nanoparticles (FNP) and zinc oxide nanoparticles (ZnO nano), as well as their physiological and molecular effects following foliar application on Arabidopsis thaliana. Additionally, we explored the potential synergistic impact of combining ZnO nano with FNPs to enhance plant resilience under drought stress conditions. Chemical characterisation confirmed the successful formation of a stable FNP-ZnO aggregate. The previously established biostimulatory effects of fullerenol at micromolar concentrations were reaffirmed, highlighting its unique chemical properties. We demonstrated that a low dose (10 mg/L) of ZnO nano, used as a foliar application for the first time in Arabidopsis thaliana, positively influenced drought stress acclimatization. Our findings indicate that FNP and ZnO alleviate oxidative stress by mitigating the impact of reactive oxygen species (ROS), modulating antioxidant enzyme activities, and stabilising redox balance. Photosynthetic performance, stomatal conductance and water-use efficiency were optimized, particularly through fullerenol application, due to its unique antioxidative and hygroscopic properties. We further analyzed the expression of selected drought-response genes involved in ABA-dependent and ABA-independent water deficit acclimation in Col-0 wild-type and pp2ca-1 drought hypersensitive mutant backgrounds. Our results revealed distinct gene expression changes in response to nanoparticle treatments, demonstrating modulation of ABA signaling and stress-related transcription factors. The combined application of FNP and ZnO exhibited unique, synergistic protective effects in drought acclimation. Future research will further elucidate the direct mechanisms linking these physiological outcomes to specific nanoparticle properties, paving the way for innovative strategies in sustainable agriculture.